2008
DOI: 10.1002/sia.2831
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale elemental identification by synchrotron‐radiation‐based scanning tunneling microscopy

Abstract: Scanning tunneling microscopy (STM) combined with synchrotron radiation (SR) enabled elemental analysis on solid surfaces at an anometer scale. The principle of analysis is based on the inner-shell excitation of a specific energy level under STM observation. After first demonstrative results on a semiconductor heterointerface (Ge nanoisland on an Si(111) 7 × 7 surface), a second trial of nanoscale elemental analysis by the SR-STM system was accomplished for Cu nanodomains on a Ge(111) 2 × 8 surface. A key to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The research team utilized glass-coated W tips [41]. Saito et al showed that Cu islands (>100 nm 2 ) embedded into Ge(111) 2 × 8 surface can be spatially resolved by detecting changes in the tip current (∼10 pA) when scanned laterally [42].…”
Section: Discussionmentioning
confidence: 99%
“…The research team utilized glass-coated W tips [41]. Saito et al showed that Cu islands (>100 nm 2 ) embedded into Ge(111) 2 × 8 surface can be spatially resolved by detecting changes in the tip current (∼10 pA) when scanned laterally [42].…”
Section: Discussionmentioning
confidence: 99%
“…The details of the apparatus have been presented in our past reports. [5][6][7] The STM controller and scanner were based on a conventional STM system with a UHV chamber having a base pressure of 1 0 × 10 −8 Pa (JEOL Co., Ltd., Tokyo, Japan). The STM tip was made from tungsten wire (0.3 mm in diameter) by electrochemical etching with NaOH solution.…”
Section: Methodsmentioning
confidence: 99%
“…4 We have recently directly observed the atomic motion caused by X-ray photons in UHV using scanning tunneling microscope (STM) dedicated to in-situ observation at an SR facility. [5][6][7] In this report, we show the details on the X-ray induced atomic motion with its dependence on beam parameters such as incident energy and photon density. Also we report a method to visualize a track of the atomic motion in STM images.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that quantitative determinations of the elemental and crystal-phase content of each layer is possible by means of a combination of microbeam-based XRF and XRD tomography. Saito et al have attempted to develop a new method of STM combined with SR for elemental analysis of solid surfaces at the nanometer scale (89). They demonstrated this SR-STM system by elemental imaging of a Cu nanodomain.…”
Section: X-ray Imagingmentioning
confidence: 99%